2023
DOI: 10.3390/s23073378
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Onset of Sweating on the Sweat Lactate Threshold

Abstract: The relationship between the onset of sweating (OS) and sweat lactate threshold (sLT) assessed using a novel sweat lactate sensor remains unclear. We aimed to investigate the implications of the OS on the sLT. Forty healthy men performed an incremental cycling test. We monitored the sweat lactate, blood lactate, and local sweating rates to determine the sLT, blood LT (bLT), and OS. We defined participants with the OS during the warm-up just before the incremental test as the early perspiration (EP) group and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…After calibration using saline for 2 or 3 min, the sensor chip connected to the sensor device was attached to the superior right upper limb of the participant 13 , 14 , which was cleaned with an alcohol-free cloth. The upper arm has a high-sweat rate during physical excursions 33 .…”
Section: Methodsmentioning
confidence: 99%
“…After calibration using saline for 2 or 3 min, the sensor chip connected to the sensor device was attached to the superior right upper limb of the participant 13 , 14 , which was cleaned with an alcohol-free cloth. The upper arm has a high-sweat rate during physical excursions 33 .…”
Section: Methodsmentioning
confidence: 99%
“…Seki et al confirmed that LT calculated from sweat lactate levels during exercise was significantly associated with LT derived from blood lactate concentrations 9 . However, the same research group also reported that there were some cases in which sweat LT failed to align with blood LT, attributable to individual variations in sweat patterns 10 . Moreover, the evaluation of sweat lactate cannot be performed in scenarios where exercise occurs in cold environments, during swimming activities, or in low-intensity workouts, where sweat production is minimal or infrequent.…”
Section: Introductionmentioning
confidence: 97%